Cognitive reserve protects ALS‐typical cognitive domains: A longitudinal study. Issue 8 (22nd July 2022) - Temp, Anna G. M.; Kasper, Elisabeth; Machts, Judith; Vielhaber, Stefan; Teipel, Stefan; Hermann, Andreas; Prudlo, Johannes
Abstract: Background and Objectives: To determine whether cognitive reserve (CR) as measured by verbal intelligence quotient, educational length, and achievement protects amyotrophic lateral sclerosis (ALS) patients' verbal fluency, executive functioning, and memory against brain volume loss over a period of 12 months. Methods: This cohort study was completed between 2013 and 2016 with a follow‐up duration of 12 months. ALS patients were recruited from two specialist out‐patient clinics in Rostock and Magdeburg in Germany. Participants underwent cognitive testing and magnetic resonance imaging both at baseline and again after 12 months. The cognitive domains assessed included verbal memory in addition to executive functions such as verbal fluency, working memory, shifting and selective attention. Results: Thirty‐eight ALS patients took part; 25 patients had no cognitive impairment (ALSni), and 13 were cognitively impaired (ALSci). On average, patients lost 294 mm 3 in their superior frontal gyri, 225 mm 3 in their orbitofrontal gyri, and 15.97 mm 3 in their hippocampi over 12 months. There was strong evidence that CR protected letter fluency from further decline (Bayes factor [BF] >10) and moderate evidence that it supported learning effects in letter flexibility (BF >3). However, there is a lack of evidence supporting the notion that working memory, shifting, selective attention or verbal memory (BF = 1) are protected. Discussion: As CR is easily determined and protects ALS‐specific cognitive domains over time, it should be regarded as a valuable predictive marker.